Do Men and Women Respond Differently to Competition? Evidence from a Major Education Reform - Morin, Louis-Philippe (Journal of Labor Economics, 2015)
This paper provides new evidence of gender differences in response to increased competition, focusing on important life tasks performed in a regular social environment. The analysis takes advantage of a major education reform in Ontario that exogenously increased competition for university grades. Comparing students prereform and postreform using rich administrative data, I find that male average grades and the proportion of male students graduating “on time” increased relative to females. Further, the evidence indicates that these changes were due to increased relative effort rather than self-selection. The findings have implications for the delivery of education and incentive provision more generally.